(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article explores the digital transformation of administrative law in Uzbekistan, focusing on the interplay between digital governance, the protection of citizens’ rights, administrative transparency, and anti-corruption strategies. It investigates the structural, technological, and legal challenges that affect the quality of administrative procedures and access to justice. Drawing on comparative legal research and national policy documents, the paper formulates a model for the ethical modernization of administrative law, aligned with international standards and democratic governance principles.